The effect of digital nursing documentation simulation on nursing informatics competency - Jatnika, Galih; Yuswandi, Yuswandi; Ismafiaty, Ismafiaty; Badrujamaludin, Asep; Hadiana, Asep Id (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Nursing informatics competencies are the skills and knowledge that nurses must master to effectively integrate digital technology into nursing practice. Digital nursing documentation simulation is an innovative learning program that utilizes digital technology to create nursing care documentation. This allows students to train in a safe environment that reflects real life clinical conditions, with a facilitator providing feedback. Purpose: To determine the effect of digital nursing documentation simulation on nursing informatics competency. Method: A quasi-experimental design with a pretest and posttest one-group design. The population was 22 undergraduate nursing students enrolled in the Faculty of Health Sciences, Jenderal Achmad Yani University, year level 4th, with a sample size of 22 participants. The digital nursing documentation simulation was administered in three stages: orientation to digital nursing documentation learning, completing nursing care documentation using a computer-based application program, and evaluation and feedback. Nursing informatics competency among nursing students was compared before and after the intervention using the Self-Assessment Informatics Competency Scale (SICS). Data were analyzed using the Wilcoxon test. Results: The average informatics competency before the intervention was 3.32, while the average informatics competency after the simulation was 3.59. There was a significant effect of digital nursing documentation simulation on nursing informatics competency (p value: 0.014). Conclusion: The application of digital nursing documentation simulation has a positive impact on Nursing Informatics Competency, especially in nursing students, in implementing nursing care.